2009
DOI: 10.1016/j.virol.2008.11.025
|View full text |Cite
|
Sign up to set email alerts
|

EBV LMP-2A employs a novel mechanism to transactivate the HERV-K18 superantigen through its ITAM

Abstract: EBV encodes latent membrane protein (LMP)-2A that functions as a homologue of the activated BCR. We have previously shown that LMP-2A transactivates a human endogenous retrovirus, HERV-K18, in infected B-lymphocytes. The Env protein of HERV-K18 encodes a superantigen that strongly stimulates a large number of T cells. To delineate the mechanism through which LMP-2A transactivates HERV-K18 env, we tested a panel of tyrosine mutants of LMP-2A in a murine B lymphoma that stably harbors HERV-K18. Our analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
1
37
0
1
Order By: Relevance
“…In addition to the mentioned viruses, retroviruses have been implicated in HL pathogenesis [37]. Interestingly, links between putative HL-associated viruses (EBV, HHV6, TTV) and endogenous retroviruses have been established [38][42]. EBV and HHV6 can induce expression of endogenous retroviruses [37], [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the mentioned viruses, retroviruses have been implicated in HL pathogenesis [37]. Interestingly, links between putative HL-associated viruses (EBV, HHV6, TTV) and endogenous retroviruses have been established [38][42]. EBV and HHV6 can induce expression of endogenous retroviruses [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, links between putative HL-associated viruses (EBV, HHV6, TTV) and endogenous retroviruses have been established [38][42]. EBV and HHV6 can induce expression of endogenous retroviruses [37], [38]. High prevalence of these viruses or immunoreactivity against viral antigens in patients with autoimmune diseases including multiple sclerosis (MS) has been observed [40][42].…”
Section: Discussionmentioning
confidence: 99%
“…It is already established that herpesviruses can activate HERVs [7-9,37-40] and it is likely that reactivated herpesviruses may transactivate HERVs at the transcriptional level. Many indications also exist that herpesviruses may be involved in MS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years it has been reported that common infections of different herpesviruses such as human herpesvirus 6A (29), human herpesvirus 6B (25), and Epstein-Barr virus (EBV) (20,21,30) are able to transactivate the HERV-K18 encoded superantigen. Furthermore, in a previous study of our group (31), we described the presence of EBV in two out of 12 samples of human cartilage obtained from patients with OA, but not in controls, suggesting the risk of EBV transmission or reactivation in a subset of patients with disorders requiring tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%